Evaluation of an Extended Stroke Rehabilitation Service (EXTRAS): A Randomized Controlled Trial and Economic Analysis. Issue 12 (December 2019) - Rodgers, Helen; Howel, Denise; Bhattarai, Nawaraj; Cant, Robin; Drummond, Avril; Ford, Gary A.; Forster, Anne; Francis, Richard; Hills, Katie; Laverty, Anne-Marie; McKevitt, Christopher; McMeekin, Peter; et al.
Abstract : Background and Purpose—: There is limited evidence to guide rehabilitation to meet the longer term needs of stroke survivors. The clinical effectiveness and cost-effectiveness of an extended stroke rehabilitation service (EXTRAS) provided following early supported discharge were determined. Methods—: EXTRAS was a pragmatic parallel-group observer-blind randomized controlled trial involving 19 UK centers. Patients with stroke were individually randomized to receive EXTRAS or usual care at discharge from early supported discharge. Five EXTRAS reviews were provided by an early supported discharge team member between one and 18 months, usually by telephone. Reviews consisted of a semi-structured interview assessing progress, rehabilitation needs, and service provision, with goal setting and action planning. The primary outcome was performance in extended activities of daily living (Nottingham EADL Scale) at 24 months post-randomization. The Nottingham EADL Scale is scored 0 to 66, with higher scores indicating better performance in these activities. Cost-effectiveness was estimated using resource utilization costs and Quality Adjusted Life Years. Analyses were intention to treat. Results—: Between January 9, 2013 and October 26, 2015, 573 participants were randomized (EXTRAS, n=285; usual care, n=288). Mean 24 month Nottingham EADL Scale scores were EXTRAS (n=219) 40.0 (SD 18.1) and usual care (n=231) 37.2 (SD 18.5) giving an adjusted mean difference of 1.8 (95% CI, –0.7 to 4.2). 1155/1338 (86%) of expected EXTRAS reviews were undertaken. Over 24 months, the mean cost of resource utilization was lower in the intervention group: –£311 (–450 [95% CI, −£3292 to £2787; −4764 to 4033]). EXTRAS provided more Quality Adjusted Life Years (0.07 [95% CI, 0.01 to 0.12]). At current conventional thresholds of willingness to pay (£20 000 [28 940] per Quality Adjusted Life Years), there was a 90% chance that EXTRAS could be considered cost-effective. Conclusions—: EXTRAS did not significantly improve stroke survivors' performance in extended activities of daily living. However, given the impact on costs and Quality Adjusted Life Years, EXTRAS may be an affordable addition to improve stroke care. Clinical Trial Registration—: URL: www.isrctn.com . Unique identifier: ISRCTN45203373. Abstract : Supplemental Digital Content is available in the text.